1993
DOI: 10.1002/path.1711710413
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of oxidized low‐density lipoprotein to mouse peritoneal macrophages: An ultrastructural study

Abstract: Mouse peritoneal macrophages (MPM) were incubated in culture medium containing low-density lipoprotein (LDL), oxidized LDL (oxLDL), or as controls, for 24 h. Scanning electron microscopy of MPM exposed to oxLDL showed loss of membrane ruffles and extensive plasmalemmal 'blebbing'. Transmission electron microscopy showed changes in up to 50 per cent of the cells, including vacuolation of the rough endoplasmic reticulum and reorganization of heterochromatin in the nuclei, characteristic of apoptosis. These chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…8,11,38,39 Even though care must be exercised in extrapolating from these in vitro studies, we suggest that low doses of ox-LDL, and perhaps other modified forms, could maintain macrophage (and foam cell) survival and therefore lengthen their tenure in a lesion by suppressing the apoptotic process with possible consequences for plaque progression. Others have found that ox-LDL (Ն100 g/mL) causes apoptotic death in monocytes/macrophages in vitro, 21,22 and macrophage (foam cell) death has been proposed to contribute to the lipid core of the atheroma. 23 We found that such high ox-LDL concentrations were also toxic to BMMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,11,38,39 Even though care must be exercised in extrapolating from these in vitro studies, we suggest that low doses of ox-LDL, and perhaps other modified forms, could maintain macrophage (and foam cell) survival and therefore lengthen their tenure in a lesion by suppressing the apoptotic process with possible consequences for plaque progression. Others have found that ox-LDL (Ն100 g/mL) causes apoptotic death in monocytes/macrophages in vitro, 21,22 and macrophage (foam cell) death has been proposed to contribute to the lipid core of the atheroma. 23 We found that such high ox-LDL concentrations were also toxic to BMMs.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been suggested that ox-LDL is responsible for foam cell death. [21][22][23] Murine bone marrow-derived macrophages (BMMs) are an easily obtainable and homogeneous normal cell population that has an absolute requirement for a growth factor such as CSF-1 for its survival and proliferation. 24,25 As such, these cells are useful for the study of the survival and proliferative responses to CSFs.…”
mentioning
confidence: 99%
“…Quinn and co-workers have shown that oxidised LDL induces chemotaxis in human monocytes, with lysophosphatidyl choline being one of its active components [3,4]. Further, oxidised LDL has been shown to be toxic for a variety of cell types including smooth muscle cells, fibroblasts [5] and more recently mouse peritoneal macrophages [6,7], the macrophage-like cell line P388D1 [8] and human monocyte-macrophages [9]. However, oxidised LDL is a complex mixture of various components including lipid hydroperoxides, oxysterols and aldehydes [10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, oxLDL induces macrophage and smooth muscle cell proliferation (Yui et al, 1993;Auge et al, 1995;Biwa et al, 1998) and also macrophage viability and survival (Sakai et al, 1996;Hamilton et al, 2001). While conversely a large body of literature also exists that demonstrates the cytotoxic and/or proapoptototic effects of oxLDL (Reid et al, 1993;Dimmiler et al, 1997;Sata et al, 1998;Coles et al, 2001;Martinet & Kockx, 2001;Nahn et al, 2003;Tabas 2005;Seimon et al, 2009;Sanson et al, 2009). The reasons for these contradictory reports might be due to differences in the concentration and oxidation processes of the oxLDL used in these different studies.…”
Section: Discussionmentioning
confidence: 99%